2013
DOI: 10.1530/eje-13-0307
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Pathogenesis of type 2 diabetes in South Asians

Abstract: The risk of developing type 2 diabetes mellitus (T2DM) is exceptionally high among both native and migrant South Asians. T2DM occurs more often and at a younger age and lower BMI, and the risk of coronary artery and cerebrovascular disease, and renal complications is higher for South Asians compared with people of White Caucasian descent. The high prevalence of T2DM and its related complications in South Asians, which comprise one-fifth of the total world's population, poses a major health and socioeconomic bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 168 publications
0
54
0
Order By: Relevance
“…The present study was a novel exploration of the effects of vitamin D status on the integration of energy, glucose and lipid metabolism in GK rats, non-obese type 2 diabetic rats that have similar characteristics as Asian type 2 diabetes[29,30]. The present study demonstrated that varying dietary vitamin D intakes could modify serum 25-OH-D levels in GK rats, resulting in profound metabolic disturbances.…”
mentioning
confidence: 64%
“…The present study was a novel exploration of the effects of vitamin D status on the integration of energy, glucose and lipid metabolism in GK rats, non-obese type 2 diabetic rats that have similar characteristics as Asian type 2 diabetes[29,30]. The present study demonstrated that varying dietary vitamin D intakes could modify serum 25-OH-D levels in GK rats, resulting in profound metabolic disturbances.…”
mentioning
confidence: 64%
“…Individuals of South Asian (Bangladeshi, Indian, Nepali, Pakistani, and Sri Lankan) origins are at particular risk of severe early onset CVD and type 2 diabetes, even before the development of obesity (9)(10)(11). Metabolic risk factors such as waist circumference, dyslipidemia, and deregulation of glucose and insulin often underlie oxidative stress and atherosclerotic changes in this population (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, non-smoking diabetes patients should be significantly more prevalent in the South Asian community (Bakker et al, 2013). However, evidence suggests Caucasians with diabetes are more likely to avoid smoking, indicating better risk factor control (Chowdhury et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that not all diabetes patients benefit from access to mobile phones and computers (Holtz andLauckner, 2012, Pal et al, 2013). Although diabetes prevalence is highest in South Asians (Bakker et al, 2013) it is unclear how ICT uptake affects this surplus risk. The implication is that health providers can't be sure this population will, for example, benefit more from mobile-phone delivered rather than computer-based interventions, or vice versa, and which risk factors will be mostly affected (e.g., diet, smoking, home blood monitoring) (Pal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%